Evaluation of Primary School Teachers' Questioning Skills Regarding Teaching Geography Subjects According to Revised Bloom's Taxonomy - DEMİRBAŞ, İbrahim; DEMİR, F. Betül (Kastamonu Egitim Dergisi, 2023)
Purpose: The main purpose of geography teaching in primary school is to give students a geographical identity, to introduce and make sense of the local and global environment. Qualifying questions and geographical inquiry skills play an essential role in achieving the goals as mentioned above of geography. The purpose of this research is to determine the level of primary school teachers' questioning skills for teaching place and way-finding gains in terms of Revised Bloom's Taxonomy. The revised Bloom Taxonomy consists of six categories: knowledge, comprehension, application, analysis, synthesis, and evaluation.
Design/Methodology/Approach: The research was carried out based on the document analysis pattern, one of the qualitative research methods, by following per the purpose of the study. The research was carried out with 32 primary school teachers working in public schools in different provinces of Turkey in the 2020-2021 academic year. To collect data in the research, the "Questioning Skill Form about Finding Place and Way-finding Gains" was used. A total of 426 questions prepared by the teachers were analyzed by descriptive analysis in terms of the cognitive process dimension of the Revised Bloom Taxonomy.
Findings: In line with the data obtained and the analyzes made, determined that the questions prepared by the teachers for the location acquisitions were at a low cognitive level. In addition, determined that the questions prepared by the teachers were mainly for the steps of understanding, remembering, and applying, respectively.
Highlights: Within the scope of the results obtained, suggestions are offered for primary school teachers' tendency to create more questions about high-level cognitive areas in the teaching of place and direction, which is a functional subject, and for further research.
Keywords: 4. Education